(untitled) (Journal of Informatics Education and Research, 2025)
Under India’s National Education Policy 2024, the integration of artificial intelligence marks a groundbreaking shift, unlocking new possibilities for modernizing skill-based education. This in-depth study assesses the impact of AI-driven learning systems by analyzing implementation data from 50 educational institutions across India over an 18-month period. Utilizing advanced machine learning techniques for performance tracking and data-driven insights, the study encompassed a diverse group of 500 teachers and 5,000 students.